2021
DOI: 10.1111/jog.14573
|View full text |Cite
|
Sign up to set email alerts
|

Factors affecting Thai pregnant women's decisions concerning prenatal diagnosis and termination of pregnancy for β‐thalassemia

Abstract: Aim: To investigate the factors influencing decisions concerning prenatal diagnosis (PND) and termination of pregnancy for β-thalassemia in Thai pregnant women. Methods: A total of 142 Thai Buddhist pregnant women waiting for PND were asked to undertake semistructured interviews regarding their reasons for PND and their decisions and reasoning concerning pregnancy if the fetus was found to be affected. The interviews were analyzed using a thematic content approach. Results: Thai pregnant women accepted PND for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(50 reference statements)
0
1
0
Order By: Relevance
“…A semi-structured interview study by Phaophan et al showed that having a Buddhist background did not influence the decisions of pregnant Thai women to terminate their pregnancy when fetal ß-thalassemia was detected [ 18 ]. Nevertheless, since Buddhism has no strict guidelines on abortion issues, attitudes toward abortion appear vary between pregnant women.…”
Section: Discussionmentioning
confidence: 99%
“…A semi-structured interview study by Phaophan et al showed that having a Buddhist background did not influence the decisions of pregnant Thai women to terminate their pregnancy when fetal ß-thalassemia was detected [ 18 ]. Nevertheless, since Buddhism has no strict guidelines on abortion issues, attitudes toward abortion appear vary between pregnant women.…”
Section: Discussionmentioning
confidence: 99%